Design, numerical simulation of Jerk circuit and its circuit implementation - Mustafa, Mamat; Aceng, Sambas; Zabidin, Salleh (HIKARI Ltd., 2015)
In this paper, in order to show some interesting phenomena of three dimensional autonomous ordinary differential equations, the chaotic behavior as a function of a variable control parameter, has been studied. The complex dynamical behaviors of the system are further investigated by means of eigenvalue structures and various attractors. The chaotic system examined in MATLAB 2010. The Oscillator circuit of the chaotic system is afterwards designed by using MultiSIM software and a typical chaotic attractor is experimentally demonstrated.